DOCUMENTATION OF TRADITIONAL HERBAL MEDICINES AMONG THE INDIGENOUS MUSLIM COMMUNITIES IN UTHAMAPALAYAM, THENI DISTRICT OF TAMIL NADU, INDIA - A. M. RASHIDA BANU; R. MAHESH (The Bioscan, 2024)
To learn more about the medicinal plant knowledge and usage within the Muslim community in the research area, an ethnobotanical plant survey was carried out. The ethnomedicinal survey encompasses 73 plant species from 65 genera and 39 families that are used by the Muslim hakkims, or traditional healers, in the Uthamapalayam district of Theni district, Tamil Nadu, India. While on field trips in the study area, questionnaires and casual in-person interviews were used to gather the necessary data. The period covered by this data was July 2023–December 2023. The majority of the medicinal herbs that were gathered were used to treat wounds, jaundice, diabetes, skin infection, headaches, Urinary infection and sexual dysfunctions. The Muslim community has a systematic approach to organising its medicinal plants, which includes documenting the plant name, family name, neighbouring name(s), part(s) used, treatment method, and associated illness. Utilising statistical techniques like informant consensus factor and use value, the collected results were further discussed. Euphorbia hirta, with an ICF value of 0.92 and a UV of 0.71 for respiratory illnesses. To combat the most common ailment, it is necessary to preserve Islamic ethnomedical techniques as well as botanicals. This has forced us to return people's lives to their natural way of healing process.